2003
DOI: 10.1038/sj.gt.3302125
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced systemic transgene expression after nonviral salivary gland transfection using a novel endonuclease inhibitor/DNA formulation

Abstract: Gene transfer to the major salivary glands is an attractive method for the systemic delivery of therapeutic proteins. To date, nonviral gene transfer to these glands has resulted in inadequate systemic protein concentrations. We believe that identification of the barriers responsible for this inefficient transfection will enable the development of enhanced nonviral gene transfer in salivary glands and other tissues. One potential barrier is the degradation of plasmid DNA by endonucleases. To test this hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…It is possible that the use of more potent DNAse inhibitors, such as the aurintricarboxylic acid or its combination with Zn 2 can further increase the efficiency of transfection through electroporation, similar to the effect described on the transfection of salivary glands when naked DNA was used (Niedzinski et al 2003). Finally, it is important to stress that in the present study the possibility of gene transfer mediated by Zn 2+ is excluded by the fact that no significant differences were observed between the post (40 min exposure) and the post/ cont (48 h exposure) Zn 2+ treatments.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the use of more potent DNAse inhibitors, such as the aurintricarboxylic acid or its combination with Zn 2 can further increase the efficiency of transfection through electroporation, similar to the effect described on the transfection of salivary glands when naked DNA was used (Niedzinski et al 2003). Finally, it is important to stress that in the present study the possibility of gene transfer mediated by Zn 2+ is excluded by the fact that no significant differences were observed between the post (40 min exposure) and the post/ cont (48 h exposure) Zn 2+ treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although in rat SMGs the use of plasmid DNA alone or in combination with rAd5 has been described, neither the efficiency of transduction nor the cells expressing the transgenes were determined (11,18,29,30). Here, we show three different strategies to transduce plasmid DNA to specific compartments of the rat SMGs: 1) the use of plasmid DNA alone, which enables the expression of the reporter gene in the ID; 2) the use of plasmid DNA mixed with rAd5 particles, which facilitates the expression primarily in large ducts and, to a lesser extent, in acini; and 3) the use of plasmid DNA in combination with isoproterenol-stimulated exocytosis, which enables targeting to primarily acini.…”
Section: Discussionmentioning
confidence: 99%
“…Because they are easily accessible through the intraoral cannulation of the major excretory (Wharton's) duct, the SMGs are a useful target for transgene expression. Indeed, successful gene transfer into rat and mouse SMGs has been shown using viral-based (1,2,4,6,24,33,41) and non-viral-based (11,18,29,30) approaches. Viral vectors show diverse tropism for acinar and ductal cells in mouse SMGs.…”
mentioning
confidence: 99%
“…Numerous studies have shown successful gene transfer into both rat and mouse submandibular glands using viral-based approaches, which offer the advantage of a more robust expression of the transgenes (Andresen et al, 2009;Baum and Tran, 2006;Delporte et al, 1996;Honigman et al, 2001;Mastrangeli et al, 1994;Morita et al, 2011;Palaniyandi et al, 2011;Perez et al, 2011;Samuni et al, 2008;Wang et al, 2000;Zheng et al, 2009). However, non viral-mediated approaches have also been utilized, although limited to a small percentage of the cells in the parenchyma (Goldfine et al, 1997;Honigman et al, 2001;Niedzinski et al, 2003a;Niedzinski et al, 2003b;Passineau et al, 2010;Sramkova et al, 2009). Furthermore, the majority of the studies on rodent SGs were focused on submandibular glands and only few studies were performed in parotid glands.…”
Section: Delivery Of Molecules Drugs and Gene Transduction In The Samentioning
confidence: 99%